Experiences of paradox: a qualitative analysis of living with cancer using a framework approach. Issue 2 (16th May 2014) - Leal, Isabel; Engebretson, Joan; Cohen, Lorenzo; Rodriguez, Alma; Wangyal, Tenzin; Lopez, Gabriel; Chaoul, Alejandro
Abstract Objectives Life‐threatening diseases such as cancer represent unique traumas—compared with singular, time‐limited traumatic events—given their multidimensional, uncertain, and continuing nature. However, few studies have examined the impact of cancer on patients as a persistent stressor. The aim of this qualitative study is to explore patients' ongoing experiences of living with cancer and the changes encountered in this experience over time. Methods Written reflections to three open‐ended questions collected from 28 patients on their experience of cancer at two time points were analyzed to explore participants' experiences and perspectives over time. Content analysis using a framework approach was employed to code, categorize, and summarize data into a thematic framework. Results Data analysis yielded the thematic framework—living with paradox, consisting of four interrelated themes: sources, experiences, resolution of paradox, and challenges with medical culture/treatment. The primary theme concerned moving through a dualistic and complex cancer experience of concurrently negative and positive emotional states across the course of cancer. Conclusions Respondents indicated that cycling through this contradictory trajectory was neither linear, nor singular, nor conclusive in nature, but reiterative across time. Recognition that patients' cancer experience may be paradoxical and tumultuous throughout the cancer trajectory can influence how practitioners provide patients with needed support during diagnosis, treatment, and recovery. This also has implications for interventions, treatment, and care plans, and adequately responding to the diversity of patient's psychosocial, physical, existential, and spiritual experience of illness. Copyright © 2014 John Wiley & Sons, Ltd.